Guiding of elastic waves in a two-dimensional graded phononic crystal plate. (24th January 2017) - Guo, Yuning; Hettich, Mike; Dekorsy, Thomas
Abstract: The guiding of elastic waves in a two-dimensional graded phononic crystal plate is investigated. This effect is induced by the resonance coupling of attachments and matrix in a silicon pillar-substrate system and the resonance frequencies of guided surface modes can be tuned by tailoring the geometry and material properties of the pillars. The resonance frequencies increase with radius and Young's modulus, and decrease with height and density of the pillars, which provides several possibilities for the guiding of elastic waves. These devices show the capability of spatially selecting different frequencies into designed channels, thus acting as a phononic multi-channel filter.